Colonic ulcers in propylthiouracil induced vasculitis with secondary antiphospholipid syndrome - Gaburri, P (BMJ Group, 2005)
A 48 year old white woman was admitted to the hospital because of several bouts of migratory polyarthritis, weight loss, fever, and abdominal pain over a period of 15 months. She had been taking propylthiouracil 100 mg daily for three years for hyperthyroidism treatment. A test for antineutrophil cytoplasmic autoantibodies (ANCA) was positive with a perinuclear pattern of staining. Antiphospholipid antibodies were also detected. Colonoscopy showed several ulcers on intestinal mucosa and the biopsy specimen showed intense microscopic vasculitis. The patient is well after methylprednisolone pulse therapy and eight months of oral azathioprine. A surveillance colonoscopy showed complete healing of intestinal ulcers. No recurrence of symptoms has occurred and autoantibodies are negative, 10 months after treatment finished. The sequence of events suggests a propylthiouracil induced vasculitis p-ANCA positive and an antiphospholipid syndrome. This is the first report of colonic ulcers diagnosed and successfully treated in such circumstances.